Impact of MSME Tax Incentive Policy Affected by Covid-19 on Tax Compliance (Economic Education Analysis Journal, 2022)
This study aimed to analyze the existence of government policies regarding MSMEs Tax Incentives affected by COVID-19 on MSMEs tax compliance. This type of research was descriptive qualitative with a case study approach. All data collected in this study was obtained by conducting interviews and direct observations of MSMEs actors who applied for MSMEs tax incentives affected by COVID-19, also supported by data and interviews with the tax authorities, namely the Tax Office Purbalingga Regency. The results of this study indicated that the MSMEs tax incentive policy affected by COVID-19 had a positive effect on MSMEs tax compliance in Banjarnegara Regency. Field research conducted by researchers stated that the provision of Tax Incentives listed in PMK-44/PMK.03/2020 regarding income tax (PPh) MSMEs borne by the government in general had been able to satisfy the expectations of taxpayers, the transfer of MSMEs tax values ​​that were transferred to capital values ​​could provide a good effect for the business continuity of MSMEs actors affected by COVID-19, the businesses they ran could bounce back and from this, it is hoped that MSMEs actors can be encouraged to improve their compliance.